Voltage evolution and electrochemical behaviour of Soil microbial fuel cells operated in different quality soils. (March 2023) - Dziegielowski, Jakub; Mascia, Michele; Metcalfe, Benjamin; Di Lorenzo, Mirella
Abstract: The desire for a net-zero carbon future is a key driver for innovation in renewable energy. Amongst several emerging solutions, soil microbial fuel cells (SMFCs) pose an interesting addition as a low-cost, carbon–neutral technology. A full understanding on the electro-generative processes in SMFCs has, however, yet to be achieved, hindering the technology's translation into practical applications. In this study, an in-depth investigation into the evolution of the output voltage generated by membrane-less, flat-plate SMFCs that accounts for the contribution of both the anode and cathode potential is provided for the first time, along with a study of the influence that organic matter content and porosity in soil has on voltage dynamics. Four stages in voltage evolution over time were observed, which depended on soil properties. The content of organic matter had the greatest effect, leading to an output voltage nearly-three times higher, when it increased from 10 % to 50 %. In this case, the anode potential reached a value of −450 mV, which prompted an exponential increase in the cathode potential and led to a power density of 68 mWm −2 . The experimental findings were used to develop a novel computational model that, by predicting the electrochemical behaviour of the SMFC in different soils, becomes a powerful guide for operating strategies that can markedly enhance electricity generation. Consequently, this study sets the foundation for effective system optimisation and real applications.